Area Postrema Undergoes Dynamic Postnatal Changes in Mice and Humans - Gokozan, Hamza Numan (J Comp Neurol, 2015)
The post-natal period in mammals represents a developmental epoch of significant change in the autonomic nervous system (ANS). In this study we focus on post-natal development of the area postrema, a crucial ANS structure that regulates temperature, breathing, and satiety, amongst other activities. We find that the human area postrema undergoes significant developmental changes during post-natal development. To further characterize these changes, we utilized transgenic mouse reagents to delineate neuronal circuitry. We discovered that although a well-formed ANS scaffold exists early in embryonic development, the area postrema shows a delayed maturation. Specifically, postnatal days 0 to 7 in mice show no significant change in area postrema volume or synaptic input from PHOX2B-derived neurons. In contrast, postnatal days 7-20 shows a significant increase in volume and synaptic input from PHOX2B-derived neurons. We conclude that key ANS structures show an unexpected dynamic developmental changes during post-natal development. These data provide a basis for understanding ANS dysfunction and disease predisposition in premature and post-natal humans.